2008
DOI: 10.1136/bmj.39458.563611.ae
|View full text |Cite
|
Sign up to set email alerts
|

Familial risk of oral clefts by morphological type and severity: population based cohort study of first degree relatives

Abstract: Objective To estimate the relative risk of recurrence of oral cleft in first degree relatives in relation to cleft morphology. Design Population based cohort study. Setting Data from the medical birth registry of Norway linked with clinical data on virtually all cleft patients treated in Norway over a 35 year period. Participants 2.1 million children born in Norway between 1967 and 2001, 4138 of whom were treated for an oral cleft. Main outcome measure Relative risk of recurrence of isolated clefts from parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
162
1
22

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(199 citation statements)
references
References 17 publications
14
162
1
22
Order By: Relevance
“…Tables S4 and S5). One facial feature observed, cleft palate (CP), was seen in six unrelated ODDD individuals (3% of 177 ODDD individuals as compared to 0.05% in the general population [Sivertsen et al, 2008]). There may be clustering of Cx43 mutations associated with this feature as three of these sporadic cases have mutations (L7V, L11P, and G22E) occurring in or adjacent to the amino terminal domain, but there are different mutations in this same region (Y17S, S18P, G2V, L7V, and G21R) in each of the five families with 11 affected members that do not have CP.…”
Section: Phenotypic Features Associated With Connexin 43 Mutationsmentioning
confidence: 99%
“…Tables S4 and S5). One facial feature observed, cleft palate (CP), was seen in six unrelated ODDD individuals (3% of 177 ODDD individuals as compared to 0.05% in the general population [Sivertsen et al, 2008]). There may be clustering of Cx43 mutations associated with this feature as three of these sporadic cases have mutations (L7V, L11P, and G22E) occurring in or adjacent to the amino terminal domain, but there are different mutations in this same region (Y17S, S18P, G2V, L7V, and G21R) in each of the five families with 11 affected members that do not have CP.…”
Section: Phenotypic Features Associated With Connexin 43 Mutationsmentioning
confidence: 99%
“…The familial recurrence of NSCP is common in the literature and it is closely related to the genetic base of cleft palate, which is not completely clarified yet 25 . Our results showed that 28.1% of the subjects had a family history of cleft palate.…”
mentioning
confidence: 99%
“…5 Evidence also shows that the risk of oral clefts among first degree relatives of cases is much higher than that in the general population. 6 Risk factors such as maternal smoking, maternal age, alcohol consumption, gender, medicinal drugs, viral infection and exposure to teratogens during early pregnancy have previously been investigated. [1][2][3][4][5][6][7] Researchers have proposed some other theories to explain the origin of CLP.…”
Section: Discussionmentioning
confidence: 99%
“…6 Risk factors such as maternal smoking, maternal age, alcohol consumption, gender, medicinal drugs, viral infection and exposure to teratogens during early pregnancy have previously been investigated. [1][2][3][4][5][6][7] Researchers have proposed some other theories to explain the origin of CLP. Other associated factors are the antiepileptic drugs usage, maternal (toxoplasmosis, rubella, cytomegalovirus, herpes simplex TORCH) infections, nutritional deficiencies (especially folic acid) during pregnancy, and consanguineous marriage between the parents.…”
Section: Discussionmentioning
confidence: 99%